The effect of heat on the metallurgical structure and B-H characteristic of (stator) armature with iron-silicon alloy in electric machines - TERZİ, ÜMİT KEMALETTİN (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2010)
Coils in electric machines are varnished for insulation after winding. These varnished coils are formed in stiff construction in slots. Under heavy-duty operating conditions, all or part of some coils may be burnt or broken. Thermal method is one of several ways to remove the defective coils. In this method, current is passed through the defective coils by an autotransformer (variac) until all the varnish of the coils is burned. If all the coils are out of order, the varnish is burned by replacing the stator or armature in a burning room. Consequently, defective coils in the stator (armature) slots can be easily removed. In this study, the latter way has been preferred and varnish of the damaged coils has been burned in a flame burning room to investigate the effect of heat on both the metallurgical structure and the magnetic characteristics of stator (armature) iron core material after removal of the defective coils. The relation between the magnetic characteristics and the metallurgical structure of the material and their solutions have been examined under laboratory conditions.
Keywords: Heat effect on material; magnetic (B-H) characteristic; microstructure of material; removal of the burned windings